Relationship between smartphone addiction, personality traits and cyberloafing behaviour among Malaysian youths/ Radiyatul Adawiyah ... [et al.] - -, Radiyatul Adawiyah; Azizan, Azliyana; Sahar, Ana; Herawati, Isnaini (Universiti Teknologi MARA, 2023)
As the number of internet users continues to grow, smartphone addiction has become a significant problem among today's youths. This addiction is exacerbated by cyberloafing and personality traits, which can negatively impact productivity and efficiency in educational settings. The purpose of this study is to examine the relationship between smartphone addiction, personality traits, and cyberloafing behaviour among Malaysian youth. The study involved a sample of 150 urban youths aged 18 and above living in the Klang Valley area. Participants completed three questionnaires, the Short Form Smartphone Addiction Inventory Scale, Mini-International Personality Item Pool, and Cyberloafing Scale via an online survey. SPSS was used to analyse the data. The results showed that males had a higher level of smartphone addiction. Additionally, extraversion and conscientiousness were found to be strongly correlated with smartphone addiction. While cyberloafing behaviour was positively correlated with extraversion traits, there was no significant correlation with smartphone addiction. In conclusion, young adults with an extraversion personality trait are at a higher risk of smartphone addiction and cyberloafing activities. For future investigations, the effects of the endemic COVID-19 on smartphone addiction should be explored to discover other problematic Internet use behaviour.